Inflammatory cytokines in newborn infants. Issue 5 (1998) - Sarandakou, A.; Giannaki, G.; Malamitsi-Puchner, A.; Rizos, D.; Hourdaki, E.; Protonotariou, E.; Phocas, I.
Abstract : Serum levels of IL-1β, IL-6 and TNF-α were measured in 48 healthy, termed neonates on the 1st (N1), 5th (N5) and 40th (N40) day after birth, compared with those in maternal serum (MS), umbilical cord (UC) and adult controls. Cytokine values in N1 and N5 were significantly elevated, than those in UC and in controls( p < 0.0001 ) . IL-1β and IL-6 declined significantly from N1 to N40( p < 0.0001 ), while TNF-α increased significantly from N1 to N5 and declined thereafter. MS∞ IL-1β and IL-6, but not MS∞ TNF-α, were significantly higher than those of controls( p < 0.0001 ) . IL-1β values depended on the mode of delivery. In conclusion, the increased concentrations of IL-1 β, IL-6 and TNF-α during the perinatal period might suggest their involvement in an inflammation like process during normal parturition, and reflect also a newborn immune response to the stress of delivery and environmental changes.